2011
DOI: 10.1007/s10530-011-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Drought-tolerance of an invasive alien tree, Acacia mearnsii and two native competitors in fynbos riparian ecotones

Abstract: Invasive alien plants (IAPs) have successfully invaded many riparian zones in South Africa, especially Australian Acacia spp. which are prevalent along riverbanks in the south-western Cape of South Africa. This Mediterranean-type climate region is predicted to endure severe future water shortages under likely scenarios of increased population growth and climate change, and IAPs aggravate this problem due to their profligate water use. Acacia mearnsii competes aggressively with native species, however, it remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Thus, invasive species maintain a higher tolerance to environmental stress factors than native and exotic non-invasive congeners. Other studies also have found that invasive species have a higher tolerance to various stress factors compared with native species [73], [74], [75], [76], [77] and their native conspecifics [24], [78]. Due to their high tolerance to salinity [37] and herbivory stress [35], some invasive species have successfully invaded harsh habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, invasive species maintain a higher tolerance to environmental stress factors than native and exotic non-invasive congeners. Other studies also have found that invasive species have a higher tolerance to various stress factors compared with native species [73], [74], [75], [76], [77] and their native conspecifics [24], [78]. Due to their high tolerance to salinity [37] and herbivory stress [35], some invasive species have successfully invaded harsh habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Duke (1983) reported that it can tolerate an annual precipitation of between 660-2280 mm, an annual mean temperature of 14.7-27.8 °C, and a pH of 5.0-7.2. The GISD says that it does not grow well on very dry or poor soils, however, Crous et al (2012) reported that it is highly drought-tolerant, able to withstand low minimum water potentials, and can utilize a large proportion of soil water.…”
Section: Acacia Mearnsiimentioning
confidence: 99%
“…A number of traits contribute to A. mearnsii's invasiveness, including rapid growth and the ability to produce of large amounts of seeds within a year (Moyo & Fatunbi, 2010), high capacity of seedling recruitment, drought-tolerance (Crous, Jacobs, & Esler, 2012), deployment of a wide crown spread to shade other plants (Costermans, 1994), and the ability to change soil properties (Boudiaf et al, 2013). However, the species is vulnerable to grass competition at a young age (NAFA, 2013), which may partly explain why it rarely successfully establishes on undisturbed soils.…”
Section: Species Descriptionmentioning
confidence: 99%